A new potential energy surface for the ground state of the LiH2+ system and dynamic studies on LiH+(X2Σ+) + H(2S) → Li+(1S) + H2(X1Σ+g). Issue 12 (20th January 2017) - Dong, Man; Li, Wentao; He, Di; Chen, Maodu
Abstract : An accurate potential energy surface for the ground state of the LiH2 + system is constructed with the neural network method. Abstract : The dynamic properties of the title reaction calculated by classical and quantum methods show large deviations from each other, whereas for the barrierless and exothermal reaction two methods should show good agreement. In order to further investigate the reaction mechanism of the title reaction, a global PES for the electronic ground state was constructed. The energy points are calculated by the multireference configuration interaction method with aug-cc-pVQZ and cc-pwCVQZ basis sets for H and Li atoms, respectively. The neural network approach is adopted in the fitting process. The classical and quantum methods are applied in the dynamic calculation based on the new PES. As expected, the dynamic properties obtained by these two methods are in good agreement with each other. In addition, two reaction mechanisms were found. When the energy is below 0.2 eV the insert reaction mechanism is dominant, and this changes to the abstract reaction mechanism as the energy increases.